If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 15t + -1(t + -4) = 0 Reorder the terms: 15t + -1(-4 + t) = 0 15t + (-4 * -1 + t * -1) = 0 15t + (4 + -1t) = 0 Reorder the terms: 4 + 15t + -1t = 0 Combine like terms: 15t + -1t = 14t 4 + 14t = 0 Solving 4 + 14t = 0 Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + 14t = 0 + -4 Combine like terms: 4 + -4 = 0 0 + 14t = 0 + -4 14t = 0 + -4 Combine like terms: 0 + -4 = -4 14t = -4 Divide each side by '14'. t = -0.2857142857 Simplifying t = -0.2857142857
| 7a+4a+a=7-19 | | 3(2-c)-c= | | 3x+7y=15 | | 5+2n+2= | | 8x-(4x+4)=12 | | 7(6)+6y=42 | | 7x+(-11x)= | | 7x+(-11)= | | y=2[3x-(4x-6)]-5(x-6) | | 8t+12t=120 | | 8(3x-9)=2(12x+7) | | 6x^2=x+15 | | 15y-45=30y | | 3x+6x=9 | | -3=a^2-3a+6 | | 0.0625x^4-0.1625x^2-0.9375=0 | | (6v-2y-3)(4v+5y)= | | 49-64u^2= | | (v-2)(7v+4y+7)= | | 2+3(3b+9)-b= | | x(x)-4x+3=1 | | x(x)-4x+3=0 | | solvex^2+4x+6=0 | | g(-3)=.33-1.33(3) | | 6/4=x/238 | | -6=x/2-4 | | r/3=39/65 | | f/5=16/40 | | f/5=39/65 | | 16a^2(1-a^2)=0 | | 2.7/3.0=w/3.6 | | h(x)=3x |